Proteomics data in support of the quantification of the changes of bovine milk proteins during mammary gland involution - Irina Boggs; Brad Hine; Grant Smolenski; Kasper Hettinga; Lina Zhang; Thomas T. Wheeler (Data in Brief, 2016)
Here we provide data from three proteomics techniques; two-dimensional electrophoresis (2-DE) followed by identification of selected spots using PSD MALDI-TOF MS/MS, one-dimensional gel electrophoresis followed by LC-MS/MS analysis of gel slices (GeLC) and dimethyl isotopic labelling of tryptic peptides followed by Orbitrap MS/MS (DML), to quantify the changes in the repertoire of bovine milk proteins that occurs after drying off. We analysed skim milk and whey sampled at day 0 and either day 3 or day 8 after drying off. These analyses identified 45 spots by MALDI-TOF, 51 proteins by GeLC and 161 proteins by DML, for which the detailed data work-up is presented as three Excel files. The data supplied in this article supports the accompanying publication “Changes in the repertoire of bovine milk proteins during mammary involution” (Boggs et al., 2015) [1]. Data are available via ProteomeXchange with identifiers ProteomeXchange: PXD003110 and ProteomeXchange: PXD003011. Keywords: Host defence, Dairy, Drying off, Proteomics